Comprehensive Expression Profile Analysis of Neutrophil Extracellular Trap-Affected Genes in Gastric Cancer Cells and the Clinical Significance of lncRNA NEAT1-Related Signaling - Li, Changjian; Zou, Xiaoming; Cai, Qingxin; Li, Jiacheng; Yang, Shifeng; Zhang, Ange; Chen, Chongyan; Zhu, Lei (Frontiers in Oncology, 2022)
Background Gastric cancer (GC) is the fifth most common malignant tumor and the third leading cause of cancer-related deaths worldwide. Neutrophil extracellular traps (NETs) can enhance the invasion of GC cells and are associated with poor prognosis in patients. However, its mechanism of action is not completely understood. Methods The content of NETs in the peripheral blood of patients with GC was detected by enzyme-linked immunosorbent assay. GC AGS cells were treated with or without NETs for 24 h. High-throughput RNA sequencing was performed to screen differentially expressed long non-coding RNAs (lncRNAs), microRNAs (miRNAs), and messenger RNAs (mRNAs). Real-time polymerase chain reaction (PCR) was used to verify gene expression. A competing endogenous RNA (ceRNA) regulatory network was constructed. Modules were screened using the molecular complex detection (MCODE) plug-in. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes enrichment analyses were performed using the genes in the network. The role and clinical significance of the lncRNA NEAT1-related signaling pathway were validated. Results The content of NETs in the patients with GC was significantly higher than that in healthy controls and was also higher in patients with high-grade (stages III and IV) GC. NETs promoted the invasion of AGS cells. A total of 1,340 lncRNAs, 315 miRNAs, and 1,083 mRNAs were differentially expressed after NET treatment. The expression of five genes was validated using real-time PCR, which were in accordance with the RNA sequencing results. A ceRNA regulatory network was constructed with 1,239 lncRNAs, 310 miRNAs, and 1,009 mRNAs. Four genes (RAB3B, EPB41L4B, ABCB11, and CCDC88A) in the ceRNA network were associated with patient prognosis, with RAB3B being the most prominent and with signaling among the lncRNA NEAT1, the miRNA miR-3158-5p, and RAB3B. NEAT1 was upregulated in AGS cells after NET treatment. RNA interference of NEAT1 inhibited the invasion of AGS cells induced by NETs, inhibited miR-3158-5p expression, and promoted RAB3B expression. NEAT1 and RAB3B expression were positively correlated in patients with GC. Furthermore, RAB3B was upregulated and miR-3158-5p was downregulated in GC tissues compared with adjacent normal tissues, which was also associated with cancer stage. Conclusion This study provides a comprehensive analysis of differentially expressed genes in NET-treated GC cells and validated the clinical significance of NEAT1-related signaling.